OP38 Improving The Patient Centricity Of Value Assessments: A Rubric. (2017) - Perfetto, Eleanor; Oehrlein, Elisabeth; Boutin, Marc; Reid, Sarah; Gascho, Eric
Abstract : INTRODUCTION: Value frameworks, analogous to Health Technology Assessment (HTA) internationally, have emerged in the United States to aid stakeholders in assessing the value of new treatments. Since patient perspectives on value may differ significantly from other stakeholders, formalized procedures to involve patients in their work have been created. Despite these efforts, concerns persist that patient involvement is insufficient or "rhetoric." To assist in this effort, the National Health Council (NHC) created a rubric to aid decision makers in improving the patient centricity of their value assessments. METHODS: A convenience sample of twenty-eight organizations was invited to participate in a roundtable discussion. Participants discussed experiences with value frameworks; debated and thematically grouped hallmark patient-centeredness characteristics; and developed illustrative examples of the characteristics. These materials were organized into the rubric, and subsequently vetted via multi-stakeholder peer review. RESULTS: Participants agreed upon six key domains of patient centeredness: partnership (patients are involved in every step of development/dissemination processes), transparency (assumptions/inputs are disclosed in an understandable, timely way), inclusiveness (perspectives drawn from broad range of stakeholders), diversity (differences in subpopulations, trajectory of disease, and stage of a life should be accounted for), outcomes (includes those that patients have identified as important), and data (variety of credible data sources are used allowing for timely incorporation of new information and account for the diversity of patient populations and patient-centered outcomes). The Rubric describes each domain and includes illustrative examples of how patient engagement/centeredness can be operationalized through direct and indirect pathways. CONCLUSIONS: The NHC Rubric is a first step toward creating patient-centered value assessments that patients and their families can rely on. It is intended to assist all stakeholders, especially the patient community, in assessing the level of patient centeredness and engagement in a given framework or model. It can be a guide to support developers in conceptualizing plans for meaningfully engaging patients.